Equine infectious anemia prevalence in urban pulling horses in the municipality of Florencia (Caqueta) - Patiño-Quiroz, Beatriz Elena; Baldrich-Romero, Nicolás Ernesto; Caicedo-Robayo, Juan Carlos; Ome-Peña, Harrinson; Murillo-Rojas, Juan Camilo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In the study, was evaluated the prevalence of equine infectious anemia (EIA) in traction horses in the municipality of Florencia, looking for relationship by sex, age, body condition and racial communes. 128 blood samples were collected from horses (103 males and 25 females) who attended four animal health brigades carried out by the hotbed research in horses ”S|EQLIUS" of the University of Amazonia, during the period between May 2014 and December 2015. The samples were analyzed in laboratory with agar gel immunodiffusion test. Descriptive statistical analysis and chi—square test (P <0.05) was performed. The data show the prevalence found IEA, determining that 26 % of the animals were positive to the disease (31.1 % of males and 4% of females). Regarding body condition, 21 horses classified in grade 2, and 47.62 % of them tested positive for EIA; in grade 3 were found the largest population (82 horses), with positive 18.29 %, and grade 4, 25 animals with positive 17.97 %; significant relationship between body condition and the prevalence of IEA was found. The prevalence in animals under 5 years (< 5) was 5%; in over 10 years (> 10) was 14.29 %, and animals between 5 and 10 years was considerably higher, 33.33 %. Environmental and socio-economic conditions facilitate transmission of the virus between horses of the same trade and any equine management system and production in the area, which would generate economic and livestock of importance to the equine industry losses.